About photometric determination of cyanides using chloroamine and pyridine-barbituric reagent - V. B. Dorogova; L. A. Dedkova (Acta Biomedica Scientifica, 2013)
The physical-chemical investigation on studying the influence of different concentrations of the barbituric acid. used in the photometric procedures on determining the cyanides, on the development and. stability of the potassium cyanide solution dyeing has been performed. The well-known methods on determining the cyanides in the air of the working zones, in the atmospheric air and in the drinking water were used as the material for studying. In these methods the photometric determination of the cyanides is based on the Kennig reaction. This reaction is also used to guantitative determining the rhodanides. The procedure analysis has shown that the researchers used the 6 % and. 3 % solutions of barbituric acid to perform the reaction for the quantitative measurement of the cyanides in different media. It was experimentally revealed that using the 3% solution of barbituric acid for the reaction, painting the potassium cyanide solution may reach the maximal value 5 minutes after the experiment start and. it was found to be stable for 40 minutes. Using the 6 % solution of barbituric acid, the potassium cyanide solution color was more found to be unstable. As a result of the experiments which were performed according to the methodical instructions on measuring the concentrations of the harmful substances in the air of the working zone, the concentration was chosen which would provide the optimal conditions for developing the color and. stability of the painted complex formed. The trueness of the results obtained was confirmed by the calculations of the average quadratic declination (S) and. the molar coefficient of the light absorption. (E). The spectroscopic character of potassium cyanide solution, painted was assessed. It was found that the optical density of the cyanide solution painted is recommended to measure at one of three wave lengths - 584, 586 and 588 nm in its photometric determination with the use of chloroamine, pyridine and barbituric acid. The other composition of the pyridine - barbituric reagent in which the 1 % barbituric acid solution is used was offered. This modification in the composition of the pyridine - barbituric reagent may provide the condition in which the colour of the final reaction product may be stable for 2 hours, which may exert the positive influence on both the quantitative measurements of cyanide in the sample and. in the reagent economy.